Validation of PRISM (Pictorial Representation of Illness and Self Measure) as a novel visual assessment tool for the burden of suffering in tinnitus patients - Peter, Nicole (Health Qual Life Outcomes, 2016)
BACKGROUND: Chronic subjective tinnitus is a frequent condition that affects the subject’s quality of life. The lack of objective measures of tinnitus necessitates the use of self-reporting and often time-consuming questionnaires for evaluating tinnitus severity. The Pictorial Representation of Illness and Self Measure (PRISM) is a two dimensional pictorial method to assess the burden of suffering. Patients illustrate their burden of suffering by the distance from a “self” to an illness circle, whereby a shorter distance indicates a higher burden of suffering. The aim of this prospective observational study was to validate the burden of suffering measured with PRISM in tinnitus patients by comparing it with different standardized questionnaires currently used in tinnitus evaluation. METHODS: A total of 188 patients filled out an online-based survey including sociodemographic variables and the following questionnaires: Tinnitus Handicap Inventory (THI), Tinnitus Questionnaire (TQ), WHO Quality of Life-Questionnaire (WHOQOL-BREF), and the Beck Depression Inventory (BDI). The subtle differences in the burden of suffering were accessed by using PRISM as an iPad version. Based on PRISM performance patients could easily be assigned in three groups, these being mildly, moderately, or severely affected akin to the standard questionnaires. RESULTS: The burden of suffering measured with PRISM correlated with the tinnitus severity (THI and TQ), depressive symptoms (BDI), and health related quality of life (WHOQOL-BREF) (all p ≤ 0.001). In the three PRISM groups tinnitus severity (THI and TQ), and depressive symptoms (BDI) differed significantly (all p ≤ 0.01). CONCLUSION: PRISM is an easily understood and time saving method for the assessment of burden of suffering in tinnitus patients. In daily clinical practice PRISM can help to identify patients with decompensated tinnitus that require more intensive treatment.